Analisis Konflik Pertanahan Masyarakat (Studi Kasus Ringroad Jalan Pangeran Suryanata Kota Samarinda) - Azhari, Tengku Deva Marisa; Budiman, Budiman (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This study aims to determine the causes and efforts to resolve land conflicts on the Ringroad Jalan Pangeran Suryanata Samarinda. The method used in this study is descriptive qualitative. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that the cause of land conflicts on the Ringroad Jalan Pangeran Suryanata Samarinda City is due to the lack of communication between the community and the government and the existence of previous conflicts that have not been resolved where this conflict has existed since 12 years ago. In an effort to resolve land conflicts on the Ringroad Jalan Pangeran Suryanata Samarinda City, the government uses the mediation method. Compensation payments are made by the government to landowners who have complete land documents and have been decided by the court. The role of the government is very much needed and important in resolving land conflicts on Jalan Ringroad, Samarinda City. The government carries out compensation payments according to its promise. Landowners appreciate the government's actions because they have paid in full the rights of residents who were previously neglected.